Appropriate Antenatal Counseling Questions for Pregnant Women with fetal Congenital Anomalies at Selected Hospitals in Addis Ababa: Clients’ and Counselors’ Perspectives - Sebsibie, Melat; jara, Dube; kebede, birhanu; Gelan, Eyob (Ethiopian Journal of Reproductive Health, 2026)
ABSTRACT Objective: To evaluate clients’ and counselors’ perspectives on appropriate antenatal counselling questions for pregnant women with fetal congenital anomalies in Ethiopia. Methods: A facility based mixed qualitative and quantitative cross-sectional study, conducted in three high volume hospitals in Addis Ababa, Ethiopia. Eight clients and 251 counselors were included in the study. Counselors had graded each question from an internationally validated QUOTE prenatal questionnaire in a 1 to 4 scale based on their judgment as to the relevance of each question in the context of our clients. Clients also had undergone an in-depth interview about the components of the questionnaire to check for its applicability. Descriptive statistics, Cronbach’s coefficient alpha reliability analysis and face validity tests were used for quantitative data and thematic analysis was done for the qualitative data. Result: The response rate was 88%, Cronbach’s alpha was 0.914 making all of the questions reliable. From the 38 questions, 32 were labeled as valid by our counselors and we identified three themes: (1) Questions from the tool which are asked and got understood by the clients, (2) Questions which are asked but was not clear for the clients and (3) Questions which are not asked to the clients at all. Questions which were valid by the counselors were also well understood by the clients. Conclusion: Most of the counseling questions from QUOTE prenatal questionnaire were found to be appropriate for use in our setting by our counselors. Additionally, the questions considered important were also well understood by the clients.